1987
DOI: 10.1099/0022-1317-68-4-1209
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the Respiratory Syncytial Virus 22K Protein Revealed by Western Blotting with Monoclonal Antibodies

Abstract: SUMMARYRespiratory syncytial (RS) virus-infected HeLa, HEp-2, Veto and BS-C-1 cell lysates were electrophoresed on SDS-polyacrylamide gels under reducing conditions and analysed by Western blotting and immunoperoxidase using monoclonal antibodies specific for the 22K protein (relative tool. wt. of 23000 in our gel system). Three novel polypeptides with mol. wt. of 24000, 21000 and 17000 were stained in addition to the 23 000 polypeptide which was present in the greatest amount in all three virus strains tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
5
14
0
1
Order By: Relevance
“…M2-1 carrying this mutation showed no detectable differences in their physical interaction with the N protein in rA2-C96G-infected cells. As reported previously, several forms of M2-1 with distinct electrophoretic mobilities are present in RSV-infected cells (22). Under reducing conditions two major species of M2-1 proteins can be detected, and the slower migrating form was found to be phosphorylated (14).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…M2-1 carrying this mutation showed no detectable differences in their physical interaction with the N protein in rA2-C96G-infected cells. As reported previously, several forms of M2-1 with distinct electrophoretic mobilities are present in RSV-infected cells (22). Under reducing conditions two major species of M2-1 proteins can be detected, and the slower migrating form was found to be phosphorylated (14).…”
Section: Discussionsupporting
confidence: 77%
“…Previously it was reported that multiple forms of M2-1 protein could be distinguished by differences in their electrophoretic mobilities on SDS-polyacrylamide gels (22). Recently it was also shown that both phosphorylated and nonphosphorylated forms of the M2-1 protein migrated with different gel mobilities under reducing conditions (14).…”
Section: Effects Of M2-1 Mutations On Processive Rna Transcription Inmentioning
confidence: 99%
“…Such a system would take advantage of naturally occurring variation among isolates, and would be applicable to studies ofmolecular epidemiology and pathogenesis. Evidence of both structural and antigenic variation among isolates has been reported in both subgroups (16,17,19,20,25,(27)(28)(29)(30)(31)(32)(33), suggesting that sufficient variation may exist to make fingerprinting possible. The recent finding of 4% nonhomology in the nucleotide sequences ofmRNAs encoding for the G glycoprotein ofthe A2 and Long strains ofsubgroup A RS virus (34) also supports the possibility of unique identification of strains.…”
Section: Introductionmentioning
confidence: 99%
“…Although, it has not been directly demonstrated that this motif in M2-1 binds zinc, it is apparent that maintenance of the motif is required for activity. The M2-1 protein in RS virus-infected cells exists in different phosphorylation states, resulting in its migration as at least two bands by reducing sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (15,23,30); the slower-migrating species contains the majority of the phosphorylated form, and the faster-migrating species lacks significant phosphorylation. The sites of M2-1 phosphorylation were recently reported as threonine 56 and serine 58 (9).…”
mentioning
confidence: 99%